Factors affecting attitudes of cocoa farmers towards replanting and decisions to replace cocoa with other crops in the Kwaebibirem District, of the Eastern Region, Ghana - Kumi, John Adu (University of Cape Coast, 2004)
The fast drift of cocoa farmers towards the cultivation of citrus or oil palm in the Kwaebibirem District is a complex phenomenon. Several factors of economic and social nature contributes to the farm level decisions affecting cocoa replanting. The focus of this study, therefore, was to investigate the factors affecting attitudes of cocoa farmers in the Kwaebibirem District towards replanting and their decisions to replace cocoa with other crops. A descriptive-correlational design was used for the survey. Data and information were gathered from 258 cocoa farmers, 37 extension agents and 20 non-cocoa growers, through the administration of questionnaires, personal interviews, and observation. Models were extracted from the analyzed data to obtain predictors of factors that determine attitudes or decisions of the cocoa farmers. A stepwise regression of the independent variables on attitudes of cocoa farmers towards replanting cocoa picked farm inputs availability, size of household, and experience in cocoa farming as predictors. All three predicting variables explained 32.2% variance in the attitudes of cocoa farmers. Farm inputs availability alone contributed 18.7% variance, whilst size of household, and experience in cocoa farming accounted for 7.8% and 5.7% variance respectively. Experience with cocoa extension agents, educational level of the cocoa farmers, and size of household, influenced knowledge on which the cocoa farmers based their decisions. Farmers had not been educated enough on cocoa replanting. As many as 79% of the cocoa farmers were not well informed about cocoa replanting. Cocoa farmers who had been educated on the replanting of cocoa were more enthusiastic to replant cocoa than those that had little or no knowledge concerning cocoa replanting. There was a high consistency in agreement (X = 3.02, S.D. = 0.91) to responses from the farmers. The fast drift of cocoa farmers towards the cultivation of citrus or oil palm in the Kwaebibirem District is a complex phenomenon. Several factors of economic and social nature contributes to the farm level decisions affecting cocoa replanting. The focus of this study, therefore, was to investigate the factors affecting attitudes of cocoa farmers in the Kwaebibirem District towards replanting and their decisions to replace cocoa with other crops. A descriptive-correlational design was used for the survey. Data and information were gathered from 258 cocoa farmers, 37 extension agents and 20 non-cocoa growers, through the administration of questionnaires, personal interviews, and observation. Models were extracted from the analyzed data to obtain predictors of factors that determine attitudes or decisions of the cocoa farmers. A stepwise regression of the independent variables on attitudes of cocoa farmers towards replanting cocoa picked farm inputs availability, size of household, and experience in cocoa farming as predictors. All three predicting variables explained 32.2% variance in the attitudes of cocoa farmers. Farm inputs availability alone contributed 18.7% variance, whilst size of household, and experience in cocoa farming accounted for 7.8% and 5.7% variance respectively. Experience with cocoa extension agents, educational level of the cocoa farmers, and size of household, influenced knowledge on which the cocoa farmers based their decisions. Farmers had not been educated enough on cocoa replanting. As many as 79% of the cocoa farmers were not well informed about cocoa replanting. Cocoa farmers who had been educated on the replanting of cocoa were more enthusiastic to replant cocoa than those that had little or no knowledge concerning cocoa replanting. There was a high consistency in agreement (X = 3.02, S.D. = 0.91) to responses from the farmers.
xviii,294p:,ill